The Influence of Viral Marketing, Influencer Marketing, and Consumer Reviews on Purchase Decisions for La Roche-Posay Products: A Study of La Roche-Posay Users in Tulungagung - Nila Nafisatul Bashiroh; Sulistiyah Sulistiyah; Lina Trisnawati; Aina Izzati Zuhria (Brilliant International Journal Of Management And Tourism, 2025)
The development of digital technology drives changes in consumer behavior in the process of searching for information and making purchasing decisions, especially for skincare products. La Roche-Posay as one of the international dermocosmetic brands has experienced increasing popularity in Indonesia along with the development of viral marketing, influencer marketing, and consumer reviews on various digital platforms. This study aims to analyze the influence of Viral Marketing, Influencer Marketing, and Consumer Reviews on Purchasing Decisions of La Roche-Posay products in Tulungagung. The approach used is quantitative research with an associative research type. The population in this study were La Roche-Posay product users in Tulungagung, with a purposive sampling technique and a total of 100 respondents. Primary data were obtained through the distribution of Likert scale questionnaires and analyzed using multiple linear regression. The results showed that Viral Marketing, Influencer Marketing, and Consumer Reviews had a positive and significant effect both partially and simultaneously on Purchasing Decisions. The coefficient of determination (R²) value of 0.63 indicates that the three independent variables are able to explain 63% of the purchasing decision variables, while the rest is influenced by other factors outside the research model. These findings confirm that digital marketing strategies through viral content, influencers, and consumer reviews play a crucial role in increasing skincare product purchasing decisions in the digital era, particularly for the La Roche-Posay brand in Tulungagung.